A pilot study: Digestion inhibiting effect of silver birch in moose - Rehbinder, C.; Sunnerheim, K.; Bratt, K.; Cedersmyg, O. (Rangifer, 2002)
A pilot study: Digestion inhibiting effect of silver birch in moose